The perceived nature and function of planning by domain-related experts: Academic, business, lay, and teacher. - Herbert, Margaret E. (University of Ottawa (Canada), 1996)
It is the underlying postulate of the present research that planning is a skill which enjoys a common mental representation and vocabulary across groups in society. Should this be the case, it may be beneficial to focus instruction on planning, as a vehicle for teaching and operationalizing metacognitive skills. Exploration of this postulate necessitates a fuller understanding of how both the nature and the function of planning are perceived by various representative groups. A deeper awareness of planning knowledge held by domain-related experts has potential to reveal similarities and dissimilarities of mental representations of planning. Toward this end, four groups of experts in academics from cognitive science, business, everyday life-planning, and teaching were provided with input from a telephone survey of the general public through a Delphi Methodology. The reiterative, three round process was undertaken by the participants to explore what is meant by the term planning, how it is done, and where and when it is used. This self-correcting technique permitted each group to generate an excellent and precise definition of planning, to clearly define the terminology used, and to articulate the functions of planning and their contextual applications. The Delphi Method achieved unusually high degrees of agreement both within and across cells as to the nature and function of planning. Additional comments from respondents brought elaboration of their perceptions to light for the purposes of understanding and comparison. There was a remarkable correspondence between the most recent literature on planning and the knowledge base of the respondents. The data confirm that there is a striking convergence, within and across the sampled groups about what planning is and the purposes for which it is used. For all cells, definitions of planning achieved a solid consensus and an impressive 97% agreement on all components of the definition and their descriptors, 89% on the function statements, and 95% for the 159 function descriptors. The analysis of data highlighted areas of similarity and dissimilarity of perceptions on aspects of planning. Cell differences between the Academic, Business, Lay, and Teacher cells were observed and reported. The findings substantiate the proposed use of planning and its vocabulary to assist learners to discuss, comprehend, and employ the underlying metacognitive thinking skills involved for problem solving in school and in real life situations throughout the life span. This valuable connector between ages and contexts has been under-utilized to date. The results of the present study justify planning as an umbrella process for instruction in metacognition. (Abstract shortened by UMI.)
Keywords: Education, Educational Psychology.